Restoring biodiversity using mammal-free sanctuaries: implications for birds and seed dispersal - Bombaci, Sara, author; Pejchar, Liba, author (Colorado State University. Libraries, 2017)
Many birds on islands are threatened by invasive mammal predators. In New Zealand, conservation organizations have constructed a network of ‘mammal-free sanctuaries,’ which exclude invasive mammals with predator-proof fencing and provide opportunities to conserve native birds. We assessed the effectiveness of these sanctuaries for restoring bird communities and bird-mediated seed dispersal. We compared the density and diversity of birds, foraging rates, and the densities of bird-dispersed seeds between mammal-free sanctuaries and paired unprotected sites. We found 0.5-4.0 times higher densities of native bird species, higher bird diversity, higher foraging rates, and higher densities of bird-dispersed seeds in sanctuaries compared to unprotected sites.
044 - Sara Petrita Bombaci
New Zealand's eco-sanctuaries restore native bird diversity and seed dispersal
Keywords: conservation; invasive species; birds; seed dispersal; restoration